ECONOMIC CONTRACTS: NOTIONS, SIGNS AND CONDITIONS OF CONCLUSION - Kozyreva, Valentyna P.; Myniuk, Olena Yu. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article deals with the theoretical and legal concepts of economic contracts, determination of their legal nature, special features and conditions of their conclusion. Methods: the study was conducted using scientific and classical knowledge methods. Using the method of generalization, an analytical study was carried out and the concept of «economic contract» was defined by scientists. Using the comparative method, the peculiarities of the conclusion of an agreement and features of economic contracts have been considered. Results: the own concept of an economic contract is provided. Different concepts of scientists have been analyzed; a subject, contents and essential conditions of economic contracts’ conclusion have been defined. Discussion: the issue of the lack of definition of the concept of «an economic contract» at the legislative level and in the Economic Code of Ukraine.